Local two-dimensional distribution of propagation speed of myocardial contraction for ultrasonic visualization of contraction propagation. (11th June 2019) - Hayashi, Akane; Mori, Shohei; Arakawa, Mototaka; Kanai, Hiroshi
Abstract: The propagation of myocardial contraction caused by the conduction of electrical excitation in the heart has been visualized in our previous study. However, it was assumed that the contraction propagated parallel to the heart wall and the propagation speed was constant within the measurement area. In the present study, we estimated the two-dimensional propagation speed of contraction at each local area by ultrasonic measurement, and examined the mechanism of the contraction propagation in the heart by calculating the spatial distribution of the propagation speed vectors. By applying the proposed method to the interventricular septum of the human heart, the propagation speed in the lateral direction was approximately 1.6 times faster than that in the beam direction. The significant difference in propagation speeds between the specialized and ordinary myocardia was detected successfully. This study suggests that the proposed method can detect the myocardial ischemic and arrhythmia regions non-invasively.